The surprise pathology—Primary squamous cell carcinoma of the colon—A case report. (2020) - Ali Husain, Aysha Hassan; Kaundinya, Kiran B.; Hammed, Faizal; Al Sayed, Abdul Rahim
Highlights: Squamous cell carcinomas – primary is very rare in occurrence in the colorectal carcinoma group. They are either found independently or along with adenocarcinomas. They may be associated with metaplastic changes seen in inflammatory bowel disease or certain helminthiasis. They may have locoregional infiltration causing micro abscess or perforations. They are aggressive and may progress to deterioration early. Abstract: Introduction: Primary squamous cell carcinomas are rare in the colon. Identified as colonic growths causing obstructive or ulcerative features, they are treated like usual colonic adenocarcinomas until the surprise findings on histopathology. A thorough search for possible primary with colonic metastasis is warranted prior to confirmation of diagnosis. They can coexist with adenocarcinomas and ulcerative colitis. We present this case with intent to add to existing literature the presentation and catastrophic clinical course of the disease in our patient. Clinical findings: The patient presented with obstructive pattern of a colonic growth with rapid weight loss. There was no family history of colonic disease and the patient did not suffer from inflammatory bowel disease. Diagnosis and therapeutic intervention: CT Scan of the abdomen revealed the growth which was infiltrating the abdominal musculature causing micro abscess formation. Colonoscopy was inconclusive as the growth was not passable enough to obtain enough biopsy for pathology. The patient underwent surgery for removal of tumor and the histopathology revealed the squamous cell carcinoma. Through the course of patient's recovery in hospital thorough evaluation was done to identify primary in sites mainly the urogenital tract. The patient was discharged and unfortunately succumbed to her disease at home before definitive treatment could be given. Conclusion: Squamous cell carcinomas in the colon warrants extensive search for the primary and coexistent adenocarcinomas or ulcerative colitis. In patients who recover from surgery, chemoradiation directed towards the pathology should be initiated to prevent rapid deterioration as in our case. Its presentation may be exophytic infiltrating surrounding structures and micro abscesses or perforations may also be encountered. We add our case report to the existing literature of primary squamous cell colon carcinoma series.